Postoperative circulating tumor DNA testing based on tumor naïve strategy after liver metastasis surgery in colorectal cancer patients - Jiang, Huiqin; Huang, Fei; Yang, Yihui; Chen, Xinning; Shen, Minna; Zhang, Chunyan; Pan, Baishen; Wang, Beili; Guo, Wei (Frontiers in Oncology, 2023)
Objective There is still a lack of highly sensitive methods for monitoring recurrence of colorectal cancer patients after liver metastasis surgery. The aim of this study was to evaluate the prognostic value of tumor-naive ctDNA detection after resection of colorectal liver metastases (CRLM). Methods Patients with resectable CRLM were prospectively enrolled. Based on the tumor-naive strategy, NGS panels containing 15 colorectal cancer hotspot mutated genes were used to detect ctDNA 3-6 weeks after surgery. Results A total of 67 patients were included in the study, and the positive rate of postoperative ctDNA was 77.6% (52/67). Patients with positive ctDNA had a significantly higher risk of recurrence after surgery (HR 3.596, 95% CI 1.479 to 8.744, P = 0.005), and a higher proportion relapsed within 3 months after surgery (46.7% vs 3.8%). The C-index of postoperative ctDNA in predicting recurrence was higher than that of CRS and postoperative CEA. The nomogram combining CRS and postoperative ctDNA can improve the accuracy of recurrence prediction. Conclusion Tumor-naive ctDNA detection can detect molecular residual lesions in patients with colorectal cancer after liver metastasis, and its prognostic value is superior to conventional clinical factors.